Education at the end of history: A response to Francis Fukuyama. Issue 2 (28th January 2021) - Ward, Sophie
Abstract: By 1989, fascism had long been defeated in Europe, and reforms in the Soviet Union appeared to signify the collapse of communist ideology, prompting Francis Fukuyama to famously declare the 'end of history'. Since then, neoliberalism has been rolled out globally. This paper argues that, with regard to higher education, Fukuyama's claim that the pursuit of knowledge will be replaced by the 'satisfaction of sophisticated consumer demands' is prescient. What, then, prompted Fukuyama to qualify his predictions in 2018? Citing both the turmoil of Brexit and the election of Donald Trump, Fukuyama blames identity politics for the breakdown of consensus over what the nation is, or should be, and suggests that the promotion of creedal identity might rescue Western democracy from populism. This paper disagrees: using the examples of Brexit and the promotion of Fundamental British Values in schools, it argues that creedal identity has become another expression of populism. Rejecting the claim that identity politics are the ultimate source of populism, it argues that populism is the predictable outcome of recession in the market economy.